A comparison between simulated and field-measured conflicts for safety assessment of signalized intersections in Australia. (April 2019) - Guo, Yanyong; Essa, Mohamed; Sayed, Tarek; Haque, Md. Mazharul; Washington, Simon
Highlights: Trajectory-based calibration of simulation model parameters for safety analysis is investigated. Automated computer vision techniques are used to extract vehicle trajectories and traffic conflicts. High correlation between simulated and field-measured conflicts was found after calibration. The results show that using simulation to evaluate safety without proper calibration should be avoided. The calibration parameters varied considerably among different traffic environments. Abstract: The primary objective of this study is to investigate the relationship between field-measured conflicts and simulated conflicts estimated from the surrogate safety assessment model (SSAM) for two signalized intersections in Brisbane, Australia. Traffic video data collected from the two signalized intersections (left-hand traffic regulations) were used for analysis. Automated computer vision analysis techniques were used to extract vehicle trajectories and identify field-measured conflicts. Simulated conflicts were obtained using VISSIM and SSAM tool. A two-step calibration procedure was performed to test the correlation between simulated and field-measured conflicts. In addition, the spatial distributions of simulated and field-measured conflicts were compared. Finally, the calibration results for the left-hand traffic environment were compared with results for signalized intersections in Canada and China (right-hand traffic environment). The results indicated a good correlation between simulated and field-measured conflicts, especially at higher TTC thresholds. However, major differences between field-measured and simulated conflict spatial distributions indicate that despite the good correlation obtained via calibration, simulated conflicts do not adequately capture the actual conflict occurrence mechanism. It was also found that there were significant differences between the left-hand and right-hand traffic environments calibration results.